Gas Chromatographic Determination of α-Keto Acids in Pharmaceutical Preparation Using 1,2-Propylenediamine as Derivatizing Reagent - Abbasi, K.U.; Khuhawar, M.Y.; Mahar, K.P.; Mallah, Arfana; Nawaz Siyal, A. (Asian Journal of Chemistry, 2012)
Analytical procedure has been developed for the gas chromatographic separation and determination of a-keto acids: pyruvic acid, 2-ketobutyric acid, 3-methyl-2-oxobutyric acid, 3-methyl-2-oxovaleric acid, 4-methyl-2-oxovaleric acid, 2-ketohexanoic acid and phenylpyruvic acid after derivatization with 1,2-propylenediamine from the column HP-5 (30 × 0.32 mm i.d). The detection was made by flame ionization. Linear calibration curves were obtained within 9.0-84 μg/mL and detection limits within 3.0-5.6 μg/mL of each a-keto acids. A pharmaceutical preparation ketosteril was analyzed for phenylpyruvic acid, 3-methyl-2-oxovaleric acid, 4-methyl-2-oxovaleric acid and 3-methyl-2-oxobutyric acid and the found amounts correlated with the labeled values. The extraction recovery from pharmaceutical preparation tested by standard addition of these compounds was calculated to be 94.0-96.8 % with RSD 0.1-0.8 %. A number of pharmaceutical additives and amino acids added did not affect the determination of a-keto acids with relative error within ± 3 %.